Levels of platinum group elements and rare-earth elements in wild mushroom species growing in Poland - Mleczek, Mirosław; Niedzielski, Przemysław; Kalač, Pavel; Siwulski, Marek; Rzymski, Piotr; Gąsecka, Monika (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2016)
Due to limited data-describing abilities of mushrooms to accumulate platinum group elements (PGEs) and rare-earth elements (REEs), the aim of this study was to determine, by inductively coupled plasma optical emission spectrometry followed by microwave-assisted sample digestion by nitric acid, the content of these elements in 20 mushroom species (10 above ground and 10 growing on wood), mostly edible, collected near a busy trunk road. The highest content of PGEs in above-ground mushroom species was observed in Lepista gilva and Suillus bovinus fruit bodies (0.38 ± 0.05 and 0.37 ± 0.03 mg kg(-1) DW, respectively), while in mushrooms growing on wood, the highest content was observed in Pleurotus ostreatus (0.35 ± 0.04 mg kg(-1) DW). The mean content of PGEs for both these groups was 0.23 ± 0.08 and 0.26 ± 0.07 mg kg(-1) DW, respectively. The highest content of REEs in Suillus luteus and Tricholoma equestra was 5.03 ± 0.50 and 2.18 ± 0.56 mg kg(-1) DW, respectively, but within mushrooms growing on wood in Ganoderma applanatum fruiting bodies it was 4.19 ± 0.78 mg kg(-1) DW. Mean contents of REEs were 1.39 ± 1.21 and 1.61 ± 0.97 mg kg(-1) DW in above-ground species and species growing on wood, respectively. Generally, the group of mushroom species growing on wood was capable of slightly higher accumulation of both REEs and PGEs. No limits have been established for both the groups until now.
Keywords: Agaricales; Platinum; platina; Poland; kovy vzácných zemin; Polsko; Metals, Rare Earth